Molecular detection of ALS1, ALS3, HWP1 and SAP4 genes in Candida Genus isolated from hospitalized patients in Intensive Care Unit, Tehran, Iran - Ardehali, Seyed Hossein; Azimi, Taher; Fallah, Fatemeh; Aghamohammadi, Nicka; Alimehr, Shadi; Karimi, Ahmad Moein; Azimi, Leila (Cellular and Molecular Biology, 2019)
Candida species are considered as one of the important cause of nosocomial and community infections. Candidacies are fourth caused by septicemia in some countries and possess extra cost to the health care system. The aim of this study was survey the presence of virulence factors associated with various candida geniuses in samples which have been collected from the intensive care unit. In this cross-sectional study, various clinical specimens have been collected from patients which hospitalized in the Intensive Care Unit (ICU) of Milad hospital, Tehran, Iran. The species of candida has been determined by CHROM agar. Finally, adherence factors genes and proteinase gene have been detected by PCR. In this research, 100 samples have been collected from patients that colonized with candida. C. albicans (63%) and C.glabrata (19.4%) are the most identified species, respectively. The species of four specimens have been not detected according to the color of CHROM agar candida medium and two different genus of candida has been isolated from 7 patients. The frequency of Als1, Als3, HWP1 and SAP1 genes among C. albicans was (92%), (94%), (95%) and (88%), respectively. The most detected virulence factor was HWP1 and SAP4 was the lowest one. At least two virulence factors have been detected in 95% of different Candida species that can cause invasive fungal properties. These results are important for infection control committee in the hospital because invasive fungal diseases can make a serious problem for patients that hospitalized in ICU.